The Justice system and the family : police, courts, and incarceration - Maxwell, Sheila Royo; Blair, Sampson Lee (Bingley, U.K. : Emerald Publishing Limited, 2022)
Around the globe, millions of individuals are entangled in justice systems daily. For individual offenders, contact often begins with the police, frequently leading to court involvement, and for offenders found guilty, to correctional supervision or incarceration. But how do these encounters affect the family? How do police and justice entanglements result in tremendous strains upon families economically and socially? Do they endanger family relationships? To better comprehend how involvement at any level of the justice system affects families, this multidisciplinary edited collection focuses on the justice system and the family. Chapters include topics such as how court processes impact family members and their support networks; how prolonged incarceration impacts children and parenting processes and family coping; how intimate relationships are impacted during and after incarceration including marriage, divorce and partner violence; and, whether system involvement leads to unintended consequences among family members such as heightened fear of crime and victimizations and fears of the police. An enlightening insight into the family dynamics surrounding contact with the justice system, Police, Courts, and Incarceration is interesting reading for researchers and students of family, sociology and criminology.
Chapter 1. A family affair: The effect of criminal justice processing on family relationships / Heather L. Scheuerman and Shelley Keith -- Chapter 2. Do parental monitoring habits change in response to juvenile recidivism? / Caitlin Cavanagh, Erica Dalzell, Alyssa LaBerge, and Elizabeth Cauffman -- Chapter 3. The associations between home economics education and familial risk factors for delinquency: An exploratory study / Xiaoli Su, Jacqueline McNett, Etta Morgan, and Manoj Sharma -- Chapter 4. Parents and siblings of incarcerated men: Questioning intersectionality and familial invisibility / Moran Benisty -- Chapter 5. Supporting incarcerated parents prior to reentry: A gender and racial equity-oriented lens / Robyn E. Metcalfe, Claudia Reino, Arriell Jackson, Jean M. Kjellstrand, and J. Mark Eddy -- Chapter 6. Maintaining family ties and facilitating father-child contact during jail: The role of extended kin / Britni L. Adams -- Chapter 7. The ripple-effects of carceral policy / Linda Mussell -- Chapter 8. Criminal justice contact and coresidence in young adulthood: Exploring the role of the family context / Cody Warner -- Chapter 9. Restorative justice and crime victim's family in China - a case analysis / Hong Lu, Bin Liang, and Deena DeVore -- Chapter 10. Falling through the fault lines: Victims experiencing poor and fragmented legal responses to domestic abuse in England and Wales / Mandy D. Burton -- Chapter 11. Domestic violence against LGBTQs: The promise and the challenges of the istanbul convention / Laima Vaige -- Chapter 12. Familial violence and human trafficking: Stories from India / Sharon Menezes.
Includes bibliographical references and index.
Keywords: Prisoners' families -- Social conditions; Imprisonment -- Social aspects; Family & Relationships -- General; Sociology